Solar energy, photovoltaics, and domestic hot water : a technical and economic guide for project planners, builders, and property owners - Plante, Russell H. (Russell Howard), 1947- (Academic Press, 2014)
"The direct use of solar energy has never been adopted on a worldwide scale since there have always been cheaper alternative energy sources available. It really wasn't that these sources were cheaper than the sun's energy which, after all, is free, but rather the costs of constructing devices or systems to use the sun's energy were greater than the costs needed to use the other sources that were available. The cost of conventional energy sources will continue to increase, and the reliability of foreign energy imports will continue to be questionable at best. We are overdue in making a serious effort to apply the sun's energy in order to complement a larger portion of our ever-increasing energy needs. The "first" most appropriate and cost-effective large-scale application of solar energy involves the heating of water for domestic use and the generation of electricity for grid-tied residential use"--